Mimicking gluten functionality with β-conglycinin concentrate: Evaluation in gluten free yeast-leavened breads. (April 2018) - Espinosa-Ramírez, Johanan; Garzon, Raquel; Serna-Saldivar, Sergio O.; Rosell, Cristina M.
Abstract: Fractionation of soy proteins has proved to produce protein concentrates with viscoelastic properties. In the present study, a β-conglycinin concentrate (βCC) obtained by a pH fractionation of soy flour was tested as structuring agent in gluten-free yeast-leavened bread model. A lean formulation with βCC and corn starch was used to produce gluten-free breads with two hydration conditions and three levels of protein (5%, 10% and 15%). Vital gluten was used to compare the functionality of βCC protein and its performance for breadmaking. Breads were characterized in moisture, color, textural parameters and image analysis. βCC presented lower hydration properties and higher emulsifying activity compared to vital gluten. Blends βCC:starch had higher water binding capacity compared to vital gluten blends. The hydration conditions tested affected the moisture, color and cell density of breads. Breads produced with βCC presented higher 2D area and height and presented higher crumb softness and cohesiveness, and did not present significant differences in springiness and resilience compared to vital gluten breads. The image analysis of crumbs showed higher cell density but lower porosity and mean cell areas in βCC breads. Thus, βCC proved to have potential as a structuring agent in gluten-free breads. Graphical abstract: Image 1 Highlights: The functionality of β-conglycinin concentrate was compared to gluten. Two different hydration levels for making gluten free breads were tested. Hydration level, protein type and protein concentration affected bread quality. β-Conglycinin gave gluten free bread comparable to gluten containing ones.